The College Choice Paradox; What Really Matters - Ryan, Brendan (International Journal of Educational Technology and Learning, 2018)
For many prospective college students and their families, the college admissions process is about finding a school with a good ranking and reputation and, god willing, a nationally ranked football program. These families spend countless hours researching school rankings and plotting their son’s or daughter’s entire future to ensure admission into a top-ranked institution. Although this is often done with good intention, such a process may not achieve the best results. Admission to an elite academic school is in no way a predictor of future professional success or life satisfaction. Guaranteeing success is impossible; however, students, parents and counselors can increase the chances of a student’s success by encouraging them to focus on building technical knowledge and proficiency in their core area of study, as well as actively engaging in activities which allow the student to build their interpersonal, leadership, critical thinking and written communication skills.